Pengaruh PDRB Sektor Pertanian dan Inflasi Terhadap Nilai Tukar Petani di Sumatera Utara - Simarmata, Yesi Veronika; Suharianto, Joko (Laboratorium Riset Ekonomi, 2026)
The agricultural sector is the main pillar of North Sumatra's economy, yet farmers' welfare often fluctuates due to macroeconomic dynamics. This study aims to analyze the influence of the Gross Regional Domestic Product (GRDP) of the agricultural sector and inflation on the Farmers' Exchange Rate (NTP) in North Sumatra Province. Drawing on economic welfare theory and purchasing power concepts, this study employs a quantitative method with multiple linear regression analysis using secondary time-series data. The results show that the agricultural sector's GRDP has a positive and significant effect on NTP, indicating that an increase in real production output can enhance farmers' bargaining position. On the other hand, inflation was found to have a positive but non-significant effect on NTP, suggesting a compensation effect where the rise in consumer goods prices is accompanied by an increase in commodity selling prices at the farmer level. In conclusion, agricultural sector productivity is a key factor in maintaining farmers' welfare, while price stability must be managed to prevent the erosion of rural purchasing power. Local governments are expected to continue encouraging the downstreaming of agricultural products to increase the added value received by farmers. Sektor pertanian merupakan pilar utama perekonomian Sumatera Utara, namun kesejahteraan petani sering kali fluktuatif akibat dinamika ekonomi makro. Penelitian ini bertujuan untuk menganalisis pengaruh Produk Domestik Regional Bruto (PDRB) sektor pertanian dan inflasi terhadap Nilai Tukar Petani (NTP) di Provinsi Sumatera Utara. Menggunakan landasan teori kesejahteraan ekonomi dan konsep daya beli, penelitian ini menerapkan metode kuantitatif dengan analisis regresi linier berganda menggunakan data sekunder kurun waktu (time series). Hasil penelitian menunjukkan bahwa PDRB sektor pertanian berpengaruh positif dan signifikan terhadap NTP, yang mengindikasikan bahwa peningkatan output produksi secara riil mampu meningkatkan posisi tawar petani. Di sisi lain, inflasi ditemukan berpengaruh positif namun tidak signifikan terhadap NTP, yang menunjukkan adanya efek kompensasi di mana kenaikan harga barang konsumsi dibarengi dengan kenaikan harga jual komoditas di tingkat petani. Kesimpulannya, produktivitas sektor pertanian menjadi faktor kunci dalam menjaga kesejahteraan petani, sementara stabilitas harga perlu dikelola agar tidak menggerus daya beli masyarakat agraris. Pemerintah daerah diharapkan terus mendorong hilirisasi produk pertanian untuk meningkatkan nilai tambah yang diterima petani.